Intraseasonal variation in a population of Fountainea ryphea (Cramer) (Lepidoptera, Nymphalidae) - Caldas,Astrid (1996)
A different approach was used for the key-factor method in a population study of the tropical butterfly Fountainea ryphea (Cramer, [1776]) (Lepidoptera, Nymphalidae), marking 20 artificial cohorts to identify the mortality levels and associated instars responsible for the variation in numbers within the season of occurrence, when generations overlap broadly. Highest mortality was detected during first instar in 13 cohorts; during second instar in three cohorts; third and fourth instars suffered highest mortality twice. Results showed that first instar mortality due to rainfall and predation, and parasitism on fourth instar could be the main factors promoting differences in number between cohorts throughout the season, although no density-dependent processes could be identified.